2020
DOI: 10.1152/jn.00085.2020
|View full text |Cite
|
Sign up to set email alerts
|

Force control during submaximal isometric contractions is associated with walking performance in persons with multiple sclerosis

Abstract: The variance in walking endurance and walking speed was associated with force control of the lower leg muscles during submaximal isometric contractions in individuals with multiple sclerosis (MS). In contrast, the fast walking speed of a sex- and age-matched control group was associated with the strength of lower leg muscles. These findings indicate that moderate declines in the walking performance of persons with MS are more associated with impairments in force control rather than decreases in muscle strength. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…11,12 Two of the most common symptoms in MS are fatigue and difficulties with walking. [13][14][15] The prevalence of fatigue increases with disease progression and eventually becomes a primary concern for up to 80% of the people with MS, 16 irrespective of the MS phenotype. 17,18 Fatigue is typically rated as one of the 2 most disabling symptoms by persons with MS, [19][20][21] but it is difficult to manage clinically as most individuals report that its severity varies within and across days.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Two of the most common symptoms in MS are fatigue and difficulties with walking. [13][14][15] The prevalence of fatigue increases with disease progression and eventually becomes a primary concern for up to 80% of the people with MS, 16 irrespective of the MS phenotype. 17,18 Fatigue is typically rated as one of the 2 most disabling symptoms by persons with MS, [19][20][21] but it is difficult to manage clinically as most individuals report that its severity varies within and across days.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with multiple sclerosis presented with worse FORCE CoV in the dorsiflexors at 20% MVC, in addition to a reduced walking distance during a 6-minute walk test. In addition, in the patient group an increased time to walk 25 feet was associated with a greater FORCE CoV during submaximal contractions in both muscles (Davis et al, 2020a).…”
mentioning
confidence: 78%
“…Commonly, FORCE CoV has been highlighted as a critical explanatory variable with respect to muscular performance of tasks including walking (Davis et al, 2020a), tremor (Kavanagh et al, 2016; Keogh et al, 2019), and risk of falls in older adults (Carville et al, 2007), with FORCE CoV progressively deteriorating from middle to older age (Piasecki et al, 2021). A recent study by Davis and colleagues examined plantar-flexor and dorsiflexor FORCE CoV at 10 and 20% MVC in individuals who presented with multiple sclerosis and those who did not (Davis et al, 2020a). Patients with multiple sclerosis presented with worse FORCE CoV in the dorsiflexors at 20% MVC, in addition to a reduced walking distance during a 6-minute walk test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different approaches to muscle activation estimation from MU discharge patterns were also developed, including Principal Component Analysis of smoothed MU discharge rates (Negro et al, 2009), NMF of smoothed MU discharge rates (Tanzarella et al, 2021) and Cumulative Spike Train (CST) of identified MUs (Farina et al, 2014). Indeed, studies of simultaneous MU behavior in different muscles are increasing (Héroux et al, 2014;de Souza et al, 2018;Kranjec and Holobar, 2019;Davis et al, 2020;Potočnik et al, 2020;Cohen et al, 2021;Tanzarella et al, 2021). However, to the best of our knowledge, comparisons of MU behavior in a group of simultaneously recorded skeletal muscles of older and young persons are still largely lacking.…”
Section: Introductionmentioning
confidence: 99%